Przystąpienie Stanów Zjednoczonych do Konwencji Berneńskiej - Kępiński, Marian (Wydział Prawa i Administracji UAM, 1990)
The author presents main features of the Berne Convention Implementation Act of 1989. That law changed substantially the provisions of the Copyright Act of 1976, in particular those which dealt with formalities. Remaining formalities such as copyright notice, copyright registration and deposit of the work with the Copyright Office are, generally speaking, of permissive nature i.e. they are not conditions of copyright protection. However, there are aways advantages of complying with these formalities. The second area (where the American concept of copyright needed evaluation in connection with U.S. accession to the Berne Convention was the protection of moral rights. American legislator adopted the minimalistic approach to that issue. It meant that no moral rights provisions were needed in the Copyright Act because general copyright laws and other statutes provided its effective protection. That view is somewhat confusing to the continental lawyer. The author reviews the protection of the right to paternity and the right to integrity and presents attemps to amend the Copyright Act by senator Kennedy and representative Kastenmaier who both intended to introduce the protection of moral rights for the authors of visual works. The article ends with the chronology of Polish-American copyright relations. These may be subdivided into three periods: 1) from Febr. 16, 1977 to March 9, 1977 — when mutual protection of works was based on formal reciprocity; 2) from March 9, 1977 to March 1s t, 1989 — when protection was based on the UCC; 3) from March 1s t, 1989 — when protection is based on the Berne Convention.
United States Accession to the Berne Convention